Mechanical and Physical Properties of Titanium Alloy Ti6Al4V-7Y - Md Zuki, Mohamad Hanif Hazrin (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
Ti6Al4V (grade 5) with different addition contents of wt.% yttrium (Y) element were fabricated successfully using FFC Cambridge process and the effects of Y content on the mechanical and physical properties of the alloys were investigated. Titanium alloy are broadly used in various application such as in the aerospace industries as bodies of aircraft and implants as in the biomechanical industries. The objectives of this project are to determine the mechanical and physical properties of Ti6Al4V-7Y and to identify the effect of different addition contents of wt.% Y element in the alloy. In order to determine the physical properties of Ti6Al4V-7Y, the sample was put in Variable Pressure-Field Emission Scanning Electron Microscope (VP-FESEM), X-ray Diffraction (XRD) machine and optical microscope. While Vickers Hardness tester was used to determine the mechanical properties of the alloy. The result shows that Ti6Al4V-7Y has bigger grain size than Ti6Al4V-2Y and the hardness value of Ti6Al4V-7Y is smaller than Ti6Al4V-2Y. It was observed that Ti6Al4V-7Y has porous surface. On the other hand, the diffraction peak intensities of Y2O3 phases increased with the increasing of Y content. As conclusion, the mechanical and physical properties of Ti6Al4V-7Y and the effect of different addition contents of wt.% Y element in the alloy have been investigated successfully.